THU0020 Angiogenesis in Rheumatoid Arthritis: VEGF Expression in Synovial Fluid. (23rd January 2014) - Mas, L.; Saurit, V.; Cortiñas, E.; Miretti, E.; Alvarellos, A.; Alvarellos, T.
Abstract : Background: The expansion of synovial epithelium in Rheumatoid Arthritis (RA), and the subsequent pannus invasion of underlying cartilage and bone, needs an increase in the vascular supply to the synovium. Angiogenesis is recognised as a key event in the formation and maintenance of the pannus in RA. The pro-angiogenic cytokine, vascular endothelial growth factor (VEGF), has been demonstrated to have a central involvement in the angiogenic process in RA. Objectives: We evaluated gene expression levels of a set of genes associated with angiogenesis in Synovial Fluid (SF) from RA patients compared with osteoarthritis patients. Methods: Knee SF samples were classified in two groups, Group I: RA with DAS 28 score > 5.1, high disease activity (n=10, 7F/3M, age: 56, 3 ± 20, 9, range: 17-84) and Group II: Osteoarthritis (OA, n=18, 13F/5M, age: 70, 5 ± 6, 6, range: 58-86). Levels of gene expression of three genes previously associated with angiogenesis, including pro-angiogenic factors: VEGF and Angiopoietin 1 (ANGPT-1) and anti-angiogenic factor, Thrombospondin I (TSP1) were evaluated using Quantitative Real Time PCR (QPCR). All amplifications were carried out in duplicate and threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting the corresponding β2Microglobuline (β2M) control, or ΔCt=Ct, gene - Ct, B2M . To test for differential gene expression between groups, a two sample t-test was performed to compare the ΔCt in the two groups. Results: Gene expression level is showed in table 1 . Conclusions: In the present cross-sectional study, increased levels of VEGF and decreased levels of TSP-1 were observed in RA patients. These gene expression results might be associated with increased angiogenesis in RA patients with high disease activity. References: Paleolog EM. Angiogenesis in rheumatoid arthritis. Supplement Review. Arthritis Res 2002, 4 (3): S81-S90. Afuwape AO et al. The role of the angiogenic molecule VEGF in the pathogenesis of rheumatoid arthritis. Histol Histopathol 2002, 17: 961-972. Disclosure of Interest: None Declared